Digital tools and welfare: adoption determinants among ginger producers in Southern and Central Ethiopia - Fetagn Gizachew; Berhanu Kuma; Alula Tafesse; Alemu Lambamo (Frontiers in Sustainable Food Systems)
IntroductionLow adoption rates of digital tools in agricultural extension services persisted among smallholder ginger producers in Southern and Central Ethiopia, despite their recognized benefits. This study investigated the factors that drove or hindered digital tool adoption in this context.MethodsA mixed-methods approach was used, combining qualitative interviews and quantitative data analysis. The Endogenous Switching Regression model was applied to examine the socio-economic, institutional, and technological factors affecting adoption.ResultsThe results showed that digital tool adoption significantly enhanced both agricultural productivity and household income among smallholder farmers. Key determinants included access to digital infrastructure, availability of ICT resources, and tailored extension services.DiscussionThe findings suggested a need for policies that promoted digital adoption, emphasizing infrastructure investment, expanded ICT access, and the development of specialized extension programs. These actions were seen as crucial for advancing rural livelihoods, supporting sustainable agriculture, and stabilizing the regional economy.